A study on the importance of mastering in English of an Art & Design's program student in UiTM Sarawak / Ainrafidah Bujang and Hadijah Hasbi - Bujang, Ainrafidah; Hasbi, Hadijah (2011)
This study was carried out to identify the importance on mastering in English. 30 respondents are comes from UiTM students in Kota Samarahan Campus. The research was conducted by giving out the questionnaire to respondents for different courses, age, SPM result and etcetera. A set of questionnaire were designed to gain primary data from the respondents about the factors of difficulties in mastering English in their subject course. The overall findings of the study indicates that vocabulary was the most factors that majority of students experience while achieving some certain level of performance. In conclusion, some suggestions have been made to enhance the achievement of students and recommendation for future research has also been included in the final part of the report.